ESTETIKA KENDHANGAN DALAM KARAWITAN JAWA - Slamet Riyadi (Institut Seni Indonesia Surakarta, 2013)
Kendhangan in Javanese karawitan show has an important role. The role were vary in everyshows. Kendhangan in karawitan, klenengan type, was different from kendhangan for supportingother kind of arts such as dance’s karawitan, wayang kulit’s, wayang orang, and ketoprak.Kendhangan that been played combined with other gamelan instruments without ciblon usuallywas used as the rhythm indicator. When it was included in other arts, kendhangan had doubleroles, which were as as the leader on gamelan orchestra, it had to guard the laya, and on the meantime it had to follow, to induce, to stimulate movement expressions, and to accentuate the dancemovements. The sound of kendhangan made by pengendhang has a big role in developing dramaticimpression and liven up the show. In klenengan, the function of pengendhang is not only as therhythm arranger, he also has the main role in revive and dramatize ensemble that been presented.When the pengendhang managed in maximizing his role, the show would not be boring. In assessingthe aspects, this writing is using aesthetic object approach referencing to the theory of beauty ofMonroe Beardsley, which are the measure of unity, intensity, and complexity. The following aresome aspects of the aesthetic elements forming kendhangan’s assessed value, that are: laya ,kebukan, and wiledan